Generalstabschef Werth (Honved, links) mit Halder und Ott bei den Scharfschiessübungen. Text auf der Rückseite
Generalstabschef Werth (Honved, links) mit Halder und Ott bei den Scharfschiessübungen. Text auf der Rückseite.